Sintesis Kitosan Berbasis Limbah Cangkang Udang Serta Pemanfaatannya Sebagai Bahan Pengawet Alami Daging Sapi - Fitri Endriyani; Rahmat Hidayat; Yenni Darvina; Fadhila Ulfa Jhora (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The utilization of shrimp shell waste as a source of chitosan represents a sustainable approach to developing bio-based materials while increasing the economic value of fisheries by-products. This study aimed to synthesize chitosan from shrimp shells (Litopenaeus vannamei) and evaluate its effectiveness as a natural preservative for beef. Chitosan was synthesized through deproteinization using 1 N NaOH, demineralization using 1 N HCl, and deacetylation using 50% NaOH. X-ray diffraction (XRD) analysis revealed six diffraction peaks with a dominant peak at 2θ = 19.042° and crystallite sizes ranging from 4.36 to 4.57 nm, indicating a monoclinic crystal structure. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of characteristic chitosan functional groups, including hydroxyl, amine, amide, and β-(1→4)-glycosidic bonds. Preservation performance was evaluated by immersing beef samples in 1% chitosan solution for 0, 15, 30, 45, and 60 minutes, followed by storage at room temperature for five days. The results showed that immersion treatments of 45–60 minutes were most effective in maintaining texture, odor quality, and pH stability. These findings demonstrate the potential of shrimp shell-derived chitosan as a safe, environmentally friendly, and economically valuable natural preservative.